Analisa Efisiensi Daya Solarcell dengan Integrasi Sistem Pendingin - Abid, Muhammad Suryo; Pambudi, Wahyu Setyo; Suheta, Titiek; Wati, Trisna; Munir, Misbahul (BEES: Bulletin of Electrical and Electronics Engineering, 2024)
One of the advantages of solar cells is their ability to generate electricity without creating noise or air pollution. However, they have the disadvantage of increasing temperature due to continuous exposure to solar radiation, thereby decreasing solar cell efficiency. A solution to mitigate this effect is a cooling system for solar cells. Cooling methods for solar cells consist of active and passive methods. Active cooling methods for solar cells require power consumption, necessitating analysis and evaluation of their efficiency in practical applications. This research analyzed the power efficiency of a cooling system using a water pump, peltier, and fan. The power measurements generated by the cooled solar cell produced a power efficiency of 8.64%, compared to a solar cell without cooling. Meanwhile, the average power efficiency over six data collections was 7.82%.